[Rezension von: Brian C. Etheridge]: Enemies to allies: cold war Germany and American memory - Mausbach, Wilfried (Journal of American history, 2017)
The central argument of enemies to allies is that americans have frequently employed narratives of Germany and german history for self-assurance. More precisely
Gesehen am 29.10.2018
Keywords: Rezension